2017
DOI: 10.1111/1744-9987.12581
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Predictive Factor for Abdominal Aortic Calcification in Thai Chronic Kidney Disease Patients

Abstract: Presence and severity of cardiovascular calcifications strongly predict cardiovascular morbidity and mortality in patients with CKD. This multicenter, crosssectional study primarily aimed to determine prevalence of abdominal aortic calcification (AAC) detected by plain lateral abdominal radiograph, and secondarily aimed to assess predictive factors for AAC. Patients (N = 1500), aged 18-70 years, with CKD stages 3-5D for ≥3 months prior to evaluation, were enrolled at 24 study centers in Thailand; 54.3% were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
(48 reference statements)
5
11
1
Order By: Relevance
“…We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17].…”
Section: Discussionsupporting
confidence: 88%
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80 percent [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4].…”
Section: Discussionsupporting
confidence: 85%
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80% [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4].…”
Section: Discussionsupporting
confidence: 85%
“…Infection has been shown to affect the structure of lipoproteins ( 22 , 23 ) and lipoprotein structure independent of lipoprotein concentration has also been shown to be associated with infectious risk ( 36 ). The lack of an association between lipids, and specifically LDL-C and CV outcomes, may be that non-lipoprotein-related processes associated with inflammation ( 18 , 37 , 38 ) or calcium and phosphorous metabolism ( 39 , 40 ) that play a more limited role in the general population are responsible for the large increase in CVD outcomes ( 1 ) and dominate CVD outcomes in dialysis patients, obscuring lipoprotein-related pathways of injury. Analysis of patients enrolled in the CHOICE study found that total cholesterol increased CVD risk if only subjects who were not inflamed were included in the analysis ( 37 , 38 ); nevertheless, in that study, the mortality risk for uninflamed patients with high total cholesterol was significantly less than that for inflamed patients at any level of cholesterol.…”
Section: Discussionmentioning
confidence: 99%